(untitled) (Research, Society and Development, 2025)
Panfacial fractures represent one of the most complex traumas of the craniofacial skeleton, characterized by the simultaneous involvement of two or more thirds of the face and associated with significant functional and aesthetic sequelae. This study aims to report the multidisciplinary management of a patient who suffered a severe panfacial fracture in a high-energy car accident, highlighting the therapeutic sequence adopted, the challenges faced, and the clinical outcome. The case involved a 27-year-old man with multiple trauma who presented fractures in the upper, middle, and lower thirds of the face, associated with extensive lacerations and ocular involvement. Treatment was performed in separate surgical stages with a staggered approach following the sequence from the most stable to the least stable areas, facilitating the re-anatomization of the supporting pillars of the face. Despite sequelae, such as visual loss and anosmia, satisfactory recovery of masticatory and deglutition functions was observed, favoring the patient’s social reintegration. It is concluded that the successful management of panfacial fracture cases depends on the surgeon’s experience, the careful definition of the surgical sequence, the appropriate timing of the intervention and, above all, multidisciplinary integration to optimize functional and aesthetic results.